Enterprise augmented reality projects : build real-world, large-scale AR solutions for various industries - López Benito, Jorge R.; Artetxe González, Enara (Packt Publishing, 2019)
Design end-to-end AR solutions for domains such as marketing, retail, manufacturing, tourism, automation, and training Key Features Use leading AR development frameworks such as ARCore, ARKit, and Vuforia across key industries Identify the market potential of AR for designing visual solutions in different business sectors Build multi-platform AR projects for various platforms such as Unity, iOS, and Android Book Description Augmented reality (AR) is expanding its scope from just being used in mobile and game applications to enterprise. Different industries are using AR to enhance assembly line visualization, guide operators performing difficult tasks, attract more customers, and even improve training techniques. In this book, you'll gain comprehensive insights into different aspects of developing AR-based apps for six different enterprise sectors, focusing on market needs and choosing the most suitable tool in each case. You'll delve into the basics of Unity and get familiar with Unity assets, materials, and resources, which will help you build a strong foundation for working on the different AR projects covered in the book. You'll build real-world projects for various industries such as marketing, retail, and automation in a step-by-step manner. This will give you hands-on experience in developing your own industrial AR apps. While building the projects, you'll explore various AR frameworks used in the enterprise environment such as Vuforia, EasyAR, ARCore, and ARKit, and understand how they can be used by themselves or integrated into the Unity 3D engine to create AR markers, 3D models, and components of an AR app. By the end of this book, you'll be well versed in using different commercial AR frameworks as well as Unity for building robust AR projects. What you will learn Understand the basics of Unity application development and C# scripting Learn how to use Android Studio along with ARCore and Sceneform to build AR prototypes for Android devices Enable AR experiences on the web with ARCore and WebAR Explore emerging AR authoring tools such as Augmented Class! for education Understand the differences and similarities between handheld and head-mounted display (HMD) environments and how to build an app for each target Become well versed in using Xcode with ARKit and SceneKit to develop AR portals for iOS devices Who this book is for This book is for anyone interested in emerging and interactive technologies or looking to build AR application ...